A Network-Based Startup for Recycling Electronic Waste - Dzikrillah Lazuardini, Amanna; Noerhatini, Pathmi; Haya, Bintan Z; Munaf, Dicky Rezadi (Jurnal Bisnisman : Riset Bisnis dan Manajemen, 2025)
The increasing volume of electronic waste (e-waste) in Indonesia has become a significant challenge for environmental management. Unfortunately, the existing recycling systems remain conventional and are not yet capable of maximizing material recovery from e-waste. This study, conducted in Bandung from March to August 2024, aims to explore a business model for a network-based application start-up that efficiently and transparently connects e-waste owners with recycling businesses. Through a digital approach, the proposed start-up promotes public participation while strengthening logistics and real-time waste tracking systems. Moreover, this strategy is expected to raise environmental awareness and foster circular economy practices. Regulatory support, multi-stakeholder collaboration, and fiscal incentives are crucial to scaling this initiative at the national level. The study applies a comprehensive methodology that includes defining the start-up’s vision and mission, marketing strategy through segmentation, targeting, and positioning (STP), market share projection, promotional planning, opportunity and challenge mapping using SWOT and Business Model Canvas (BMC), operational design, and business feasibility analysis.Through a digital approach, the start-up not only encourages public participation but also strengthens logistics systems and enables real-time waste tracking. Moreover, this strategy has the potential to raise environmental awareness and promote circular economy practices. Regulatory support, multi-stakeholder collaboration, and fiscal incentives are key factors for the success of this initiative on a national scale.